A Comparison of Stage Conversion in the Coccidian Apicomplexans Toxoplasma gondii, Hammondia hammondi, and Neospora caninum - Sokol-Borrelli, Sarah L.; Coombs, Rachel S.; Boyle, Jon P. (Frontiers in Cellular and Infection Microbiology, 2020)
Stage conversion is a critical life cycle feature for several Apicomplexan parasites as the ability to switch between life forms is critical for replication, dissemination, pathogenesis and ultimately, transmission to a new host. In order for these developmental transitions to occur, the parasite must first sense changes in their environment, such as the presence of stressors or other environmental signals, and then respond to these signals by initiating global alterations in gene expression. As our understanding of the genetic components required for stage conversion continues to broaden, we can better understand the conserved mechanisms for this process and unique components and their contribution to pathogenesis by comparing stage conversion in multiple closely related species. In this review, we will discuss what is currently known about the mechanisms driving stage conversion in Toxoplasma gondii and its closest relatives Hammondia hammondi and Neospora caninum. Work by us and others has shown that these species have some important differences in the way that they (1) progress through their life cycle and (2) respond to stage conversion initiating stressors. To provide a specific example of species-specific complexities associated with stage conversion, we will discuss our recent published and unpublished work comparing stress responses in T. gondii and H. hammondi.